Cognate Awareness in French Immersion Students: Contributions to Grade 2 Reading Comprehension. (2nd September 2016) - Hipfner-Boucher, Kathleen; Pasquarella, Adrian; Chen, Xi; Deacon, S. Hélène
ABSTRACT: Cognate awareness is the ability to recognize the cognate relationship between words in two etymologically related languages. The current study examined the development of cognate awareness and its contribution to French (second language) reading comprehension among Canadian French immersion children. Eighty-one students were tested at the end of Grade 1 and again at the end of Grade 2. Children were administered a cognate awareness task in French, in which they were asked to decide whether a French word had a cognate in English. Overall, performance on the cognate awareness task was significantly above chance at both time points, and it improved overtime. Thus, for the majority of the participants, cognate awareness was evident as early as first grade. Regressions revealed that cognate awareness measured in Grades 1 and 2 made a significant contribution to Grade 2 French reading comprehension, beyond multiple controls. The results of the study suggest that cognate awareness is a unique aspect of second-language reading comprehension in young bilingual children.